Vascular changes of the choroid and their correlations with visual acuity in diabetic retinopathy - Jing, Ruixia; Sun, Xiubin; Cheng, Jimin; Li, Xue; Wang, Zhen (Frontiers in Endocrinology, 2024)
Objective To investigate changes in choroidal vasculature and their correlations with visual acuity in diabetic retinopathy (DR). Methods The cohort was composed of 225 subjects (225 eyes), including 60 subjects (60 eyes) with healthy control, 55 subjects (55 eyes) without DR, 46 subjects (46 eyes) with nonproliferative diabetic retinopathy (NPDR), 21 subjects (21 eyes) with proliferative diabetic retinopathy (PDR), and 43 subjects (43 eyes) with clinically significant macular edema (CSME). Swept-source optical coherence tomography (SS-OCT) was used to image eyes with a 12-mm radial line scan protocol. Initially, a custom deep learning algorithm based on a modified residual U-Net architecture was utilized for choroidal boundary segmentation. Subsequently, the SS-OCT image was binarized and the Niblack-based automatic local threshold algorithm was employed to calibrate subfoveal choroidal thickness (SFCT), luminal area (LA), and stromal area (SA) by determining the distance between two boundaries. Finally, ratio of LA and total choroidal area (SA + LA) was defined as choroidal vascularity index (CVI). The choroidal parameters in five groups were compared, and correlations of the choroidal parameters and best-corrected visual acuity (BCVA) were analyzed. Results The CVI, SFCT, LA, and SA were found to be significantly lower compared to both healthy and without DR (P < 0.05). The SFCT was significantly higher in NPDR group compared to No DR group (P < 0.001). Additionally, SFCT was lower in PDR group compared to NPDR group (P = 0.014). Furthermore, there was a gradual decrease in CVI with progression of diabetic retinopathy, reaching its lowest in PDR group. However, CVI of CSME group exhibited a marginally closer proximity to that of NPDR group. Multivariate regression analysis revealed a positive correlation between CVI and duration of DM and LA (P < 0.05). Univariate and multivariate regression analyses demonstrated a significant positive correlation between CVI and BCVA (P = 0.003). Conclusions Choroidal vascular alterations, especially decreased CVI, occurred in patients with DR. The CVI decreased with duration of DM and was correlated with visual impairment, indicating that CVI might be a reliable imaging biomarker to monitor progression of DR.